Co-expression of CD39 and CD103 identifies tumor-reactive CD8 T cells in human solid tumors - Thomas Duhen; Rebekka Duhen; Ryan Montler; Jake Moses; Tarsem Moudgil; Noel F. de Miranda; Cheri P. Goodall; Tiffany C. Blair; Bernard A. Fox; Jason E. McDermott; Shu-Ching Chang; Gary Grunkemeier; et al. (Nature Communications, 2018)
Identifying and enumerating tumor-specific CD8 T cells are important for assessing cancer prognosis and therapy efficacy. Here the authors show that CD39 and CD103 mark a subset of tumor-infiltrating CD8 T cells that are tumor-reactive and exhibit characteristics of exhausted or tissue-resident memory T cells.